Rejuvenating The Face of Medan - Azura, Syahirah; Utami, Wahyu (Talenta Publisher, 2020)
Medan is the third-largest city in Indonesia, and so do their heritage. The historic building in Medan City is a valuable asset. These buildings have infinite value and essential to people that ever lived there. Throughout more than five generations, these shophouses are stood still until today and waiting to be eaten by age. Therefore, this area should be conserved. Buildings that lived in Pasar Hindu slowly become extinct because of ignorance from people. Thus, an act of revitalization to this place should be done to conserve the story that ever recorded in this place, so that our next generations can learn and appreciate our history. This project is about how architecture can act as preservation in the historical area throughout the environmental design by the methodological approach. Heritage is a beautiful theme that keeps the scent and the scars of old stories that ever crouched at the shophouse. Compared to other countries that have successfully rejuvenate their historic buildings, their achievements developed much more than building faÃ§ade but also increased the economic income of the community. These historical buildings had finally become a valuable asset for the owner, precious gems to the city, and pride to the nations.